1996
DOI: 10.1016/s0022-5223(96)70334-3
|View full text |Cite
|
Sign up to set email alerts
|

The additional hospital costs generated in the management of complications of pacemaker and defibrillator implantations

Abstract: The rapid approach of capitated reimbursement mandates that providers examine their practice patterns associated with all surgical procedures. Documentation of (1) the complications associated with these procedures and (2) the additional hospital costs associated with the management of these complications is critical for comprehensive fiscal accountability. This study analyzed (1) the feasibility of obtaining accurate hospital cost data specific for complications and (2) the outcome in terms of fully loaded ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 25 publications
0
46
0
1
Order By: Relevance
“…The course of untreated infections is dismal, and their management has important economic implications. 2 The estimated rate of infection after implantation of permanent endocardial leads is between 1% and 2%, although this rate varies in the literature Clinical Perspective p 1355 from 0.13% to 12.6%. [3][4][5][6][7][8][9][10][11][12][13] The files collected by the National Hospital Discharge Survey revealed that between 1996 and 2003, the rates of hospitalization for infections of implantable antiarrhythmic systems increased faster than the rates of system implantations.…”
mentioning
confidence: 99%
“…The course of untreated infections is dismal, and their management has important economic implications. 2 The estimated rate of infection after implantation of permanent endocardial leads is between 1% and 2%, although this rate varies in the literature Clinical Perspective p 1355 from 0.13% to 12.6%. [3][4][5][6][7][8][9][10][11][12][13] The files collected by the National Hospital Discharge Survey revealed that between 1996 and 2003, the rates of hospitalization for infections of implantable antiarrhythmic systems increased faster than the rates of system implantations.…”
mentioning
confidence: 99%
“…In addition, financial costs associated with ICD infection can be significant, with an average length of stay for CIED infection from 8 to 20 days and total costs from $24 000 to $130 000. 3,4,[6][7][8] …”
mentioning
confidence: 99%
“…[2][3][4] The reported average cost of combined medical-surgical treatment of an infected permanent pacemaker or implantable cardioverterdefibrillator is $24 459 and $57 213, respectively. 5 …”
mentioning
confidence: 99%